A study on the feasibility of bergamot peel oil-gasoline blends for spark-ignition engines. (10th March 2022) - Vikneswaran, M.; Saravanan, C.G.; Manickam, M.; Sasikala, J.; Femilda Josephin, J.S.; Pugazhendhi, Arivalagan; Varuvel, Edwin Geo
Abstract: In this research, an ample attempt was made to make use of oil extracted from bergamot fruit peel, which can be regarded as a renewable energy source. A systematic experimental approach was adopted to evaluate the feasibility of bergamot peel oil (BGT) as a substitute for gasoline fuel in spark-ignition (SI) engine applications. The oil derived from the rinds of the bergamot fruit was blended in gasoline on a volume basis in the ratios of 10:90, 20:80, 30:70, and 40:60 and experimentally tested in a multi-point fuel injection (MPFI) installed SI engine. The fuel properties of the BGT and its blends were tested. Endoscopic visualization technique was used to analyze the spatial flame distribution on a crank angle basis for the gasoline and bergamot blends. Also, the performance, combustion, and emission characteristics of bergamot-gasoline blends were evaluated, and the results were compared with sole gasoline at various engine brake powers. The endoscopic results revealed that bergamot-gasoline blends exhibited higher flame spread than sole gasoline. The performance study revealed that the brake thermal efficiency and specific fuel consumption exhibited by bergamot-gasoline blends were almost equivalent to that of sole gasoline. The mean in-cylinder pressure was marginally higher, and peak pressure crank angle degree was slightly advanced for bergamot-gasoline blends in comparison to that of gasoline fuel. With an increasing concentration of BGT in the blend, the hydrocarbon (HC) and carbon monoxide (CO) emission decreased at the expense of nitrogen oxides (NOx ). Furthermore, BGT exhibits a research octane number (RON) of 80 and a calorific value comparable to that of gasoline, making it a potential candidate for SI engines. From the outcome of this study, it can be concluded that BGT could be a promising alternate biofuel for the partial replacement of gasoline in SI engines. Graphical abstract: Image 1 Highlights: Oil tapped from the rinds of bergamot fruit exhibits a RON of 80. Performance of bergamot peel oil blended gasoline was studied in a SI engine. Combustion flames of test fuels were captured using combustion chamber endoscopy. BTE of bergamot peel oil blends are marginally higher than gasoline. CO and HC emissions of bergamot peel oil blends are lower than gasoline.